I love my career, don't I? the influence of organisation-based support on expatriates' adjustment and occupational withdrawal intention - Chan, H.L.; Toh, P.S.; Ng, S.I.; Zawawi, D. (Creative Commons Attribution, 2021)
Employees are encouraged to undergo expatriation to develop cross-cultural competencies that meet global workforce standards. However, most expatriates struggle to adjust and eventually withdraw from their assignments. The purpose of this paper is to empirically investigate the role of perceived organisational support (POS), host country national (HCN) support, and adjustment as antecedents of expatriates' occupational withdrawal intention. Drawing from the sampling frame of various foreign chambers of commerce, survey data were collected from 112 expatriates based in organisations in Malaysia. Partial least squares-structural equation modelling was used to test the hypotheses. Both POS and HCN support positively influence expatriate adjustment, while only POS negatively influences occupational withdrawal intention. Further, expatriate adjustment mediates the effects of POS and HCN support on occupational withdrawal intention. When expatriates adjust better upon receiving POS and HCN support, their occupational withdrawal intention is lower. This study enriches the current literature by applying the conservation of resources theory and contributes to the limited research on the roles of organisation-based support on expatriate success. The findings indicate that expatriate-hiring firms should provide suitable support mechanisms for expatriates on overseas assignments. These firms should amplify the role of HCNs to help expatriates adjust to local cultures and complete their assignments.